Personal Factors that Motivate Entrepreneurial Initiation: A Case Study of Women Entrepreneurs in San Francisco, Argentina (Perspectivas de las Ciencias Económicas y Jurídicas, 2025)
The objective of this work is to examine the determining factors of entrepreneurial motivation, with the aim of presenting a model that explains this phenomenon and subsequently enables the identification of differences between male and female entrepreneurs.The study was organized into four stages: the first involved a literature review on the evolution of research on entrepreneurial motivation; the second consisted of in-depth interviews with female entrepreneurs from the city of San Francisco to explore their life stories in relation to the emergence of their projects; third, the information was systematized through the construction of an integrated analytical model composed of dimensions, variables, and indicators that determine entrepreneurial motivation. Finally, the instrument was tested, and a factorial correlation analysis was conducted, which led to the design of new dimensions and the grouping of variables.
Keywords: entrepreneur; motivation; needs; incentives